Recovery and recycling of paper proceedings of the international symposium organised by the Concrete Technology Unit and held at the University of Dundee, Scotland, U K on 19 March 2001 - Dhir, Ravindra K.; Limbachiya, Mukesh C.; Newlands, Moray D. (Thomas Telford, 2001)
Throughout the world, a number of legislative and industry-led initiatives, aimed at value recovery from paper collected for recycling, have been introduced with a view to increasing public awareness of paper recycling and creating a sustainable environment. This title presents the proceedings of an international symposium on the topic.